The Relationship of Giving Positive Reinforcement to Group Leadership of Class X Students at SMA Negeri 3 Malinau - Diana Novita; Suprianto Suprianto; Nazwa Manurung; Irianto Aras; Ni Made Diah Padmi (Pinisi Business Administration Review, 2021)
Giving reinforcement is an important thing in the teaching process, the task of the teacher as an educator is to increase learning motivation in students, one of which is by providing stimulation in the form of awards/praises so that students can be motivated, control or change bad behavior. The purpose of this study was to determine the relationship between giving positive reinforcement to the leadership of the class X student group at SMA Negeri 3 Malinau. This study uses descriptive quantitative research, the population is 153 from class X students and the research sample is 55 students. The data collection technique used is the Likert scale on the positive reinforcement scale and the student group leadership scale. The data analysis technique used is descriptive analysis technique and inferential analysis, product moment correlation test and simple linear regression test were carried out. The results of the study obtained that the leadership level of the student group was included in the high category, namely 47.3% with a total of 26 students. The results showed that there was no relationship between  giving positive reinforcement to student group leadership.